Role of the urethral plate characters in the success of tubularized incised plate urethroplasty - Aboutaleb, Hamdy (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Today, tubularized incised plate (TIP) urethroplasty is the most commonly performed operation for distal and mid-penile hypospadias. Reports from different centers worldwide confirm its nearly universal applicability and low complications rate. AIM: Evaluation of the urethral plate characters and its effect on the outcome of TIP urethroplasty. MATERIALS AND METHODS: Between 2010 and 2013, 100 children with primary distal penile hypospadias underwent TIP urethroplasty. Urethral plates were categorized as flat, cleft, and deeply grooved. Postoperatively, patients were followed-up for evaluation of meatal stenosis, fistula formation, and glandular dehiscence at 1(st), 3(rd) and 6(th) months. Patients were followed-up for urethral calibration by urethral sound 8 Fr at 3(rd) and 6 months follow-up. Data were statistically analysed using Epi info program to correlate between the width, plate shape, and complications. RESULTS: Mean age at surgery was 4.3 years. Patients were followed-up for an average period of 6.4 months. Pre-operative location of the meatus was reported as coronal in 46, subcoronal in 50 and anterior penile in 4 cases. Urethral plate characters were flat in 26 cases, cleft in 52, and deeply grooved in 22. Urethral plate width was >8 mm in 74 cases and <8 mm in 26. Patients with urethral plate <8 mm had a statistically significant higher fistula rate (P = 0.004) and failed 8 Fr calibrations in 26.9% (P = 0.01) compared with the patients with urethral plate >8 mm. In addition, we also founds higher fistula rate and failed 8 Fr calibrations in flat urethral plate. CONCLUSIONS: An adequate urethral plate width (>8 mm) is essential for successful TIP repair. Lower success rates with flat plates may need buccal mucosal augmentation to improve the results.